ANALISIS INDEKS KERENTANAN SEISMIK, PERIODE DOMINAN, DAN FAKTOR AMPLIFIKASI MENGGUNAKAN METODE HVSR DI STAGEOF TANGERANG - Afra Kansa Maimun; Ulfa Nur Silvia; Vida Julia J.; Puji Ariyanto (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Microtremor is a natural harmonic vibration of the soil that occurs continuously with a low amplitude of about 0.1 - 1 micron. Microtremor characteristics show rock characteristics and types based on the value of its dominant period are used to analyzing the response of rocks to amplification of vibrations. In collecting microtremor data, we use the TDL 303S (Taide Digital Seismograph) equipment and the DS-4A Short Period Seismograph type seismometer with a recording duration of 30-45 minutes. Microtremor data measurements were carried out at 20 research points with a distance of 1 meter between points. Microtremor data processing until reach natural frequency values ​​(F0) using the Horizontal to Vertical Spectral Ratio (HVSR) method obtained by Geopsy software. From the results of microtremor data processing, it can be seen that the distribution of the dominant period value, amplification factor, and seismic vulnerability index (Kg) at Tangerang Geophysics Station. From this research, it is known that the average dominant period (Tdom) in Stageof Tangerang is (0.6572 seconds), the amplification factor is 2.4357, and the seismic vulnerability index (Kg) is 3.8991. This value shows that the dominant soil layer in this area is site class E alluvial soil T0> 0.6 seconds, this indicates that the soil type is very prone to earthquakes. But in terms of the seismic vulnerability index, low amplification factor, and dominant period it is relatively low so the impact is insignificant.